The economics of production factors and operational cost in medium businesses in bandung: hospitality, restaurant and beauty center - Ayuningtyas, Harvita; Budi nugroho, Anggoro (The Indonesian Journal of Business Administration, 2016)
Abstract - The Governmentâ€™s decision to raise the Basic Electricity Tariffs (BET) turns out according to party sequence is caused due to PLN from fuel price hike are getting bounced. When fuel prices go up automatically the operational cost increased so that the budget of PLN funds allocated to operating costs is insufficient. The existence of the phenomenon of increasing the fuel price, Basic Electricity Tariffs (BET) and Regional Minimum Wage (RMW) greatly affect corporate business then the author doing research on these three factors associated with the Operational Cost especially in MICE and tourism industry in Bandung. In this research, external and internal analysis is used to determine the economics situational conditions. The data are collected from ABC Hotel, DEF Restaurant, and GHI Beauty Center. The company size analysis is also used to determine which company`s category that can reflect MICE and Tourism industry`s condition. In order to find the effect of BET, RMW, and Oil price to operational cost. After doing every analysis, there is a finding that BET and RMW are have significantly positive effect with operational cost in MICE and tourism industry in Bandung. In order to reduce the operational cost in MICE and tourism industry, using the technology of electricity component such as LED light, Inverter AC, and LED TV could reduce the electricity cost significantly. Furthermore, in order to reduce RMW`s cost, force planning is used. The effect of using those ways could reduce RMW`s cost significantly. Regression analysis shows that BET has significantly positive effect to operational cost while RMW and gasoline price have no effect in ABC Hotel. In DEF Restaurant, there are no variables have positive effect. In GHI Beauty center BET and RMW have significantly positive effect to operational cost while gasoline price has no effect. In order to reduce Operational Cost, a new strategy is needed for each company. With new strategy, ABC Hotel could reduce Operational Cost as amount as 795 billion rupiah and GHI Beauty Centre could reduce Operational Cost as amount as 120 billion rupiah.Â Keywords: MICE, Tourism, Operational Cost, BET, RMW, Fuel Price